2003
DOI: 10.7589/0090-3558-39.3.712
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Parasites of Coyotes (Canis latrans) in New York based on Fecal Analysis

Abstract: Coyotes (Canis latrans) have colonized northeastern North America only within the past 10-80 yr. We examined feces of coyotes in 2000-01 at three sites in New York (USA) to survey parasites in the region. Two cestodes, nine nematodes, five protozoa, one trematode, and two arthropods were identified from 145 coyote fecal samples. Parasite component community diversity was higher (n = 16 species) in southern New York than in middle and northern sites (nine species each) and infracommunity species richness was gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 12 publications
0
28
0
4
Order By: Relevance
“…The intensity of the infection was classified on the basis of the number of adult forms of E. aerophilus in the lungs: no worms, slight (1-5 adults), mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and moderate (more than 20) infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of the infection was classified on the basis of the number of adult forms of E. aerophilus in the lungs: no worms, slight (1-5 adults), mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and moderate (more than 20) infection.…”
Section: Methodsmentioning
confidence: 99%
“…This nematode is epidemically the most important species from the Capillaria genus. It can be found in the trachea and in the great bronchi, scarcely in the nasal cavity and frontal sinuses of cats (17), dogs (27), foxes (1,25), coyotes (13), wolves (19), raccoons (23), bears, and other carnivores (6).…”
Section: Introductionmentioning
confidence: 99%
“…La prevalencia observada (36.84%) difiere mucho de las obtenidas por Gompper et al (2003) en coyotes de Nueva york (56%), así como del 72% encontrado en excretas de lobos ibéricos (Domínguez & de la Torre 2002) y del 14% en heces de lobos del Ártico (Marquard-Petersen 1997). Aunque, es común que un porcentaje de la población se encuentre sin parasitar, la incorporación de muestras viejas al análisis podría favorecer esta situación.…”
Section: Discussionunclassified
“…These helminth genera have all been recorded in closely related grey wolves, Canis lupus (Craig & Craig, 2005). Faecal samples from Arctic foxes, Vulpes lagopus, (Meijer et al, 2011;Elmore et al, 2013), and coyotes, Canis latrans (Gompper et al, 2003), have been found to contain Capillaria species. Trichuris spp., including T. vulpis, have been found in Arctic foxes (Meijer et al, 2011) and maned wolves, Chrysocyon brachyurus (Curi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Trichuris spp., including T. vulpis, have been found in Arctic foxes (Meijer et al, 2011) and maned wolves, Chrysocyon brachyurus (Curi et al, 2012). Ancylostomatid helminths (Gompper et al, 2003) and golden jackals (Dalimi et al, 2006). Hymenolepis sp.…”
Section: Discussionmentioning
confidence: 99%